Capitalism as a Mode of Power: Piotr Dutkiewicz in Conversation with Shimshon Bichler and Jonathan Nitzan - Shimshon Bichler; Jonathan Nitzan; Piotr Dutkiewicz (22 Ideas to Fix the World: Conversations with the World's Foremost Thinkers, 2013)
PREAMBLE BY PIOTR DUTKIEWICZ: In a unique two-pronged dovetailing discussion, frequent collaborators and coauthors Jonathan Nitzan and Shimshon Bichler discuss the nature of contemporary capitalism. Their central argument is that the dominant approaches to studying the market – liberalism and Marxism – are as flawed as the market itself. Offering a historically rich and analytically incisive critique of the recent history of capitalism and crisis, they suggest that instead of studying the relations of capital to power we must conceptualize capital as power if we are to understand the dynamics of the market system. This approach allows us to examine the seemingly paradoxical workings of the capitalist mechanism, whereby profit and capitalization are divorced from productivity and machines in the so-called real economy. Indeed Nitzan and Bichler paint a picture of a strained system whose component parts exist in an antagonistic relationship. In their opinion, the current crisis is a systemic one afflicting a fatally flawed system. However, it is not one that seems to be giving birth to a unified opposition movement or to a new mode of thinking. The two political economists call for nothing short of a new mode of imagining the market, our political system, and our very world.
Keywords: 330; business and industry; capital accumulation; capitalization; capitalism; class; data; differential accumulation; market system; methodology; neoclassical economics; power; systemic crisis; value theory